1996
DOI: 10.1021/jm9505066
|View full text |Cite
|
Sign up to set email alerts
|

Biarylcarboxylic Acids and -amides:  Inhibition of Phosphodiesterase Type IV versus [3H]Rolipram Binding Activity and Their Relationship to Emetic Behavior in the Ferret

Abstract: In addition to having desirable inhibitory effects on inflammation, anaphylaxis, and smooth muscle contraction, PDE-IV inhibitors also produce undesirable side effects including nausea and vomiting. In general, compounds that inhibit PDE-IV also potently displace [3H]rolipram from a high-affinity binding site in rat cortex. While this binding site has not been identified, it has been proposed to be an allosteric binding site on the PDE-IV enzyme. Preliminary studies have suggested that the emetic potency of PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
78
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(81 citation statements)
references
References 16 publications
1
78
0
Order By: Relevance
“…However, central nervous system and gastrointestinal side effects remain a problem, limiting clinical development. It has been speculated that some of the side effects may be mediated through inhibitor interaction with the high-affinity rolipram binding site (HARBS) on PDE4 (Barnette et al, 1995;Duplantier et al, 1996); rolipram and a number of other PDE4 inhibitors have been shown to bind with low nanomolar affinity to this site (Schneider et al, 1986;Torphy et al, 1992;Jacobitz et al, 1996).…”
Section: Pde4 Inhibitors Tested Were Potent Competitors For [mentioning
confidence: 99%
“…However, central nervous system and gastrointestinal side effects remain a problem, limiting clinical development. It has been speculated that some of the side effects may be mediated through inhibitor interaction with the high-affinity rolipram binding site (HARBS) on PDE4 (Barnette et al, 1995;Duplantier et al, 1996); rolipram and a number of other PDE4 inhibitors have been shown to bind with low nanomolar affinity to this site (Schneider et al, 1986;Torphy et al, 1992;Jacobitz et al, 1996).…”
Section: Pde4 Inhibitors Tested Were Potent Competitors For [mentioning
confidence: 99%
“…Because emesis is at least in part a side effect mediated by the central nervous system, new PDE4 inhibitors with low brain penetration have been developed, but this approach has not yielded better tolerated compounds, given that the area postrema, which acts as chemoreceptor trigger zone for emesis, is not protected by the blood-brain barrier and that PDE4 inhibitors also exert direct effects on the gastrointestinal tract (Okuda et al, 2009). Alternative strategies were to selectively target the low-affinity rolipram-binding site conformer of PDE4 over the high-affinity rolipram-binding conformer (Barnette et al, 1996;Rocque et al, 1997) or the isoform PDE4B over the isoform PDE4D (Robichaud et al, 2002b;Lehnart et al, 2005), but both these approaches have been only partially validated (Duplantier et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence suggesting that PDE4 inhibitors reduce EAE severity has led to the proposal that such compounds may have therapeutic potential for treating MS (Burnouf and Pruniaux, 2002). Unfortunately, a complication with many PDE4 inhibitors is their ability to readily cross the blood-brain barrier, accumulate in the CNS, and trigger nausea and emesis (Duplantier et al, 1996;Burnouf and Pruniaux, 2002). In this study, we have shown that a novel nonbrain penetrant PDE4 inhibitor, L-826,141, significantly delays the onset and severity of EAE administered either before or after the initial onset of clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Nausea and emesis remain a large concern in the development of PDE4 inhibitors (Duplantier et al, 1996). Although rodents do not vomit, it is still possible to distinguish whether the mice are experiencing discomfort as a direct result of constant central PDE4 inhibition.…”
Section: Discussionmentioning
confidence: 99%